2021
DOI: 10.1177/15569845211034506
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cryobiopsy Outside of the Operating Room: A Safe Alternative to Surgical Biopsy

Abstract: Objective Transbronchial lung cryobiopsy (TBLC) is a promising technique that can provide a histologic diagnosis in interstitial lung diseases (ILD) and is an alternative to surgical lung biopsy. The main concerns with the procedure are safety and diagnostic accuracy. The technique is applicable in patients unable to undergo surgical biopsy due to severe comorbidities or when patient transport to the operating room is dangerous. This study reports the initial experience with TBLC on a thoracic surgical service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…[16] Another retrospective study reported a 9.3% 30-day mortality in patients who underwent TBCB either without intubation and EBB positioning in the endoscopy suite or under general anesthesia through an ETT in the ICU. [17] However, this study included critical ICU inpatients and utilized both 1.9 and 2.4 mm probes, with the latter associated with a higher complication rate. [22] On the contrary, a lower incidence of pneumothorax (4%) has been described using an ultrathin 1.1 mm cryoprobe and retrieving the specimens through the working channel of the bronchoscope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Another retrospective study reported a 9.3% 30-day mortality in patients who underwent TBCB either without intubation and EBB positioning in the endoscopy suite or under general anesthesia through an ETT in the ICU. [17] However, this study included critical ICU inpatients and utilized both 1.9 and 2.4 mm probes, with the latter associated with a higher complication rate. [22] On the contrary, a lower incidence of pneumothorax (4%) has been described using an ultrathin 1.1 mm cryoprobe and retrieving the specimens through the working channel of the bronchoscope.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Although some reports exist of TBCB being performed with a flexible bronchoscope under moderate sedation and spontaneous breathing, these cases did not involve the positioning of an ETT and/or an EBB, potentially making the procedure unsafe in the event of severe bleeding because a second access through the glottis is necessary after the biopsy. [16][17][18] In this study, we propose a new technique to perform TBCB using a flexible bronchoscope and an EBB through an ETT in moderately sedated and spontaneously breathing patients, without the need for anesthesiologic assistance.…”
Section: The Authors Have No Conflicts Of Interest To Disclosementioning
confidence: 99%
“…It has shown to be an accurate and an alternate option to surgical lung biopsy in diagnosis of diffuse parenchymal lung diseases. 21 , 22 One of the major complications during a transbronchial cryobiopsy is bleeding, which can be difficult to control endoscopically. Previous studies have reported moderate-to-severe bleeding rates of up to 39%.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure requires conscious sedation or general anesthesia. It can be performed easily as an outpatient procedure in patients unable to undergo surgical biopsy due to severe comorbidities or when transfer to other hospital facilities is dangerous, such as those admitted to the intensive care unit 6 . However, there are still concerns related to potential procedural complications and the safety of TBLCs, especially for frail patients with diffuse and severe pulmonary disease, as well as concerns regarding the comparative diagnostic yield of specimens compared to surgical biopsies 7 .…”
mentioning
confidence: 99%
“…It can be performed easily as an outpatient procedure in patients unable to undergo surgical biopsy due to severe comorbidities or when transfer to other hospital facilities is dangerous, such as those admitted to the intensive care unit. 6 However, there are still concerns related to potential procedural complications and the safety of TBLCs, especially for frail patients with diffuse and severe pulmonary disease, as well as concerns regarding the comparative diagnostic DOI: 10.1097/LBR.0000000000000948 yield of specimens compared to surgical biopsies. 7 TBLC is associated with a high risk of pneumothorax (6% to 20%) and moderate or severe bleeding (requiring additional intervention as mechanical ventilation in 1.8% to 35.7%).…”
mentioning
confidence: 99%